Endless Data, Limited Insight: A Literature review of China's data system - Rauhala, Viia (2025)
China is widely recognized for its extensive data collection efforts, both within its borders and globally. However, existing research presents conflicting narratives about the motivations, goals, and the actual capabilities behind this data collection. There is little insight on the internal dynamics that shape China’s approach on data. This thesis seeks to offer a more cohesive view on China’s data collection and analysis practices by examining the strategic, political and structural conditions that influence them. Domestically, China’s data capabilities seem powerful, but there is not much reliable information on them. It has strict control over its domestic cyberspace with the goal of ensuring national security and the Chinese Communist Party’s (CCP) position in power. Internationally, China utilizes multiple techniques when collecting data including espionage, spies and businesses. There is an underlying motive to enhance the nation’s international standing as a superpower through initiatives and projects. The findings of this study highlight three core factors that influence China: governance, bureaucracy and control. Internationally, China promotes a data governance model centered on national sovereignty. Internally, its capabilities are hindered by a rigid and fragmented bureaucratic system. This all comes down to the CCP’s need for authoritarian control over the country. Understanding China’s data strategy requires an overall view on the country’s ambitions and needs. Maintaining diplomatic contact with China, especially in matters related to cyber security, is important. This does not mean that China should be blindly trusted, and the rising superpower must not be underestimated.